Long Term Results of Memotherm Stent Treatment in Patients with Recurrent Urethral Stenosis - Gunes, Ali; Ugras, Murat; Soylu, Ahmet; Kilic, Suleyman; Altinoluk, Bulent; Baydinc, Can (Annals of Medical Research, 2021)
None